2021
DOI: 10.1093/ehjcr/ytab174
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and treatment of effusive–constrictive pericarditis: a case report

Abstract: Background Effusive–constrictive pericarditis (ECP) is a rare syndrome involving pericardial effusion and concomitant constrictive pericarditis. The hallmark is a persistently elevated right atrial pressure of >10 mmHg or reduction of less than 50% from baseline despite pericardiocentesis. Aetiologies include radiation, infection, malignancy, and autoimmune disease. Case summary A 71-year-old man with a history of atri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Pericardiectomy is reserved for patients refractory to adequate anti-inflammatory therapy. Unfortunately, it has been reported that up to 16% of patients may continue to have symptoms, eventually requiring extensive pericardiectomy [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pericardiectomy is reserved for patients refractory to adequate anti-inflammatory therapy. Unfortunately, it has been reported that up to 16% of patients may continue to have symptoms, eventually requiring extensive pericardiectomy [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…It may also be diagnosed by utilizing T2-weighted cardiac MRI, which can delineate the pericardial thickening further and distinguish between edema, inflammation, and fibrosis. ECP may also help diagnose concomitant myocarditis by demonstrating typical features including myocardial injury (hyperemia, necrosis, scarring) in T1-weighted and myocardial edema in T2-weighted imaging [13][14][15]. ECP post-pericardiocentesis usually resolves either spontaneously or with medical management using NSAIDs, colchicine, or steroids for pain and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…ECP is a rare pericardial disease characterized by the coexistence of pericardial constriction and effusion. Its characteristic feature is a persistently elevated right atrial pressure of > 10 mmHg or a reduction of less than 50% from baseline despite pericardiocentesis[ 3 ]. The etiology of ECP varies, including idiopathic origin, viral origin, post-procedural origin, radiation, drug-induced, connective tissue disease, malignancy, and tuberculosis.…”
Section: Discussionmentioning
confidence: 99%
“…The present case of ECP associated with P. aeruginosa infection demonstrated that in patients with localized pericardial effusion who have typical risk factors, such as infection, prior use of antibiotics, and prior hospitalization, the presence of ECP should be highly suspected[ 3 ]. Additionally, this case highlighted the significance of sensitive recognition of the echocardiographic features of ECP, including pericardial effusion combined with atrial enlargement, which is the most intuitive feature of constrictive pericarditis.…”
Section: Discussionmentioning
confidence: 99%